If money talks, what does it say? corruption and business financing of political parties - McMenamin, Iain (Oxford Oxford University Press, 2013)
Why do businesses contribute to political parties? Is money a universal language? Do business contributions to political parties convey different messages in different countries? This book answers these questions based on intensive case studies of Australia, Canada, and Germany.
Theory and research design -- Canada : pragmatism and centrism -- Australia : pragmatism and ideological bias -- Germany : symbolic expenditure -- Widening the argument -- Money is multi-lingual.
Includes bibliographical references (pages 146-169) and index.
Keywords: Campaign funds; Corporate power; Lobbying; Political corruption; Campaign funds -- Case studies; Corporate power -- Case studies; Lobbying -- Case studies; Political corruption -- Case studies